Development of Interactive Learning Media Using the Canva Website on the Topic of Elasticity and Hooke's Law - Zahra, Alya Puspita; Wardani, Regina Bilqis; Bernardo, Rene Karlos (Program Studi Pendidikan Fisika, 2025)
This research develops Canva website-based physics learning media for Elasticity and Hooke's Law. The research focuses on introducing and utilizing the free version of the Canva website as an interactive learning media for teachers in the classroom. The practicality of this site makes it easily accessible to everyone and has a fairly wide reach. Using the Research and Development (R&D) research method, researchers used the 4-D research model, which consists of defining, designing, developing, and distributing products to prospective physics teachers to assess their feasibility. The feasibility results obtained showed about 78.94% (feasible) for the aspect of manipulating software, 80.58% (feasible) for the aspect of learning design, and 78.17% (feasible) for the aspect of visual communication. In addition, this website is feasible to use according to prospective physics teachers, and an average percentage of feasibility characterizes it at 82.23% (very feasible). It is hoped that the Canva website innovation on Elastasis and Hooke's Law material can help teachers integrate technology in education.